Organizational Communication Abstracts, analysis, and overview : V. 10 - International Communications Association; Greenbaum, Howard H.; Falcione, Raymond L.; International Communications Association (Washington : ERIC Clearinghouse, 1975)
This book consists of more than 400 annotated abstracts representing the literature produced in 1974 relevant to the field of organizational communication. The objectives of this book are to provide a general structure through which students, scholars, and practitioners might obtain comprehensive information on recently published and unpublished literature in this field; to design and implement a suitable classification system for the literature of organizational communication; and to provide abstracts of literature for the year 1974. The introduction presents a rationale for the project, a review of research methods developed by the authors for the preparation of abstracts, and a statement of limitations as to both the completeness of the coverage and the classifications of the literature. The abstracts are divided into nine classifications, with each classification further divided into two subclassifications: books and dissertations; and articles, papers, and U.S. Government publications. (Author/TS)
Microfiche.
Keywords: Abstracts; Reference Materials, Bibliographies